Population impacts of free‐ranging domestic cats on mainland vertebrates. Issue 9 (12th October 2017) - Loss, Scott R; Marra, Peter P
Abstract : Domestic cats ( Felis catus ) have contributed to at least 63 vertebrate extinctions, pose a major hazard to threatened vertebrates worldwide, and transmit multiple zoonotic diseases. On continents and large islands (collectively termed "mainlands"), cats are responsible for very high mortality of vertebrates. Nevertheless, cat population management is traditionally contentious and usually involves proving that cats reduce prey population sizes. We synthesize the available evidence of the negative effects of cats on mainland vertebrates. More than a dozen observational studies, as well as experimental research, provide unequivocal evidence that cats are capable of affecting multiple population‐level processes among mainland vertebrates. In addition to predation, cats affect vertebrate populations through disease and fear‐related effects, and they reduce population sizes, suppress vertebrate population sizes below their respective carrying capacities, and alter demographic processes such as source–sink dynamics. Policy discussions should shift from requiring "proof of impact" to a precautionary approach that emphasizes evidence‐driven management to reduce further impacts from outdoor cats.